Brazil [videorecording (DVD)] - Gilliam, Terry; Pryce, Jonathan; De Niro, Robert; Palin, Michael; Helmond, Katherine (Criterion collection, 2006)
In this surrealistic nightmare vision of a "perfect" future where technology reigns supreme, a daydreaming bureaucrat who is involved with an underground superhero and a beautiful mysterious woman becomes the tragic victim of his own romantic illusions. This is the original 142 minute director's cut edition of the film assembled from both the European and American versions.